P-101. Oral cancer incidence in Kelantan, Malaysia - Ghazali, N.; Zain, R.B.; Samsudin, A.R.; Rusdi, A.R. (Elsevier, 2001)
Aim: A pilot study was carried out in the state of Kelantan, north-east of Malaysia, to determine the feasibility of using pathological and hospital databases to acquire incidence on oral cancer. Method: Data on OC patients (ICD-10: C00.3-00.5, C02-06) were obtained from incident surgical biopsy records of the two main referral centres for head and neck surgery in Kelantan namely, the Department of Pathology, Faculty of Medicine, University of Science and the Oral Surgery clinic, Kota Baru Hospital between January 1994 to December 1998. The crude and age-specific incidence rates were calculated based on the annual population census of Kelantan and this was standardised to the world population. Results: There were forty-three OC cases during that period. The incidence of OC was 6.1 per million annually (males, 1.4 per million; females, 1.0 per million). The age-standardised incidence was 1.7 per million. The main leading sites of OC were the gum and the buccal mucosa/vestibule/retromolar areas. Conclusion: Pathological and hospital records provide an alternative way of obtaining important epidemiological data on OC, crucially in places where population-based cancer registries have not been established.